Pengaruh Disiplin Kerja Terhadap Kinerja Pegawai Pada Kantor Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kabupaten Tanjung Jabung Barat - Muhamad Efendi (Science of Management and Students Research Journal (SMS), 2019)
This study entitled the effect of work discipline on employee performance at the Regional Development Planning Agency office in Tanjung Jabung Barat Regency. The formulation of the problem in this study is how the effect of work discipline on employee performance in the BAPPEDA Districts Tanjung Jabung Barat Office. The analytical method used in this study was descriptive qualitative and quantitative with survey techniques using questionnaire data collected and then analyzed using the SPSS program analysis tool using simple linear regression and Microsoft Excel. The Regional Development Planning Board is an element of regional administration planning which has the task of carrying out the formulation and implementation of regional policies in the area of regional development planning in Tanjung Jabung Barat Regency. Work discipline and employee performance at the BAPPEDA Tanjung Jabung Barat Office conducted by BAPPEDA agency employees by using a strategy that is, giving employees time to work on worship, giving gifts to employees, giving bonuses to employees who work overtime, making employee entertainment events on major holidays, and provide rewards in the form of Umrah packages and traveling abroad to employees who have achieved good quality work. Based on the estimation results using a statistical test it is known that the prob value of 0.000 <0.5 percent or the calculated T value of 7.297> T table 1.685 then ho is rejected and ha is accepted, meaning that at a significant level of 0.5 percent the work discipline variable influences the performance of employees in the Office of BAPPEDA Tanjung Jabung Barat.